Latest Patent for Rice Transplanter Mulching Device - Wang, Yaping; Wei, Xuebing; Zhu, Xiaofei; Fan, Yuqi; Li, Shengbiao (Recent Patents on Engineering, 2025)
BackgroundThe planting technology of rice mulching and rice transplanting can effectively control weed growth, reduce fertilizer loss, maintain surface temperature, improve fertilizer utilization, reduce the use of pesticides and chemical fertilizer, and is a new mode of green rice cultivation. The rice mulching device is a key component, and the quality of its mulching directly affects the productivity and planting quality of rice. Additionally, obtaining an efficient rice transplanter with an integrated rice transplanter for transplanting and mulching is the hot spot of research in this field.ObjectiveBy analyzing and discussing the patents of rice mulching cultivation technology research and mechanical mulching devices, their development trend is summarized, which provides a reference for the development of rice transplanter mulching devices.MethodsThe research status of rice transplanter mulching devices in recent years is summarized, and various mulching devices' structure types and applications are discussed.ResultsBy summarizing the patents on rice transplanter mulching devices, the current status of patent applications was obtained, and the problems and future research direction of rice transplanter mulching devices were discussed.ConclusionIn-depth study of various types of rice transplanter mulching devices, the existing rice transplanter mulching device needs further improvement regarding the laying mechanism, the film-breaking mechanism, and the structural type of the mulching device. With the application of GPS, sensor detection, information processing, automatic control, and other technologies in agricultural machinery, rice transplanter filming is gradually developing in the direction of high speed, automation, and intelligence.
Keywords: Rice